2015
DOI: 10.1101/gad.269498.115
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the TERT promoter, switch to active chromatin, and monoallelic TERT expression in multiple cancers

Abstract: Somatic mutations in the promoter of the gene for telomerase reverse transcriptase (TERT) are the most common noncoding mutations in cancer. They are thought to activate telomerase, contributing to proliferative immortality, but the molecular events driving TERT activation are largely unknown. We observed in multiple cancer cell lines that mutant TERT promoters exhibit the H3K4me2/3 mark of active chromatin and recruit the GABPA/B1 transcription factor, while the wild-type allele retains the H3K27me3 mark of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
192
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(203 citation statements)
references
References 39 publications
11
192
0
Order By: Relevance
“…Therefore, loss of ARID1A, which frequently occurs in endometrium-related and other carcinomas, may induce an open euchromatin configuration, allowing the transcription of TERT to start. In support of the above observations, a recent study demonstrated that mutation in TERT promoter can epigenetically switch chromatin into an active mode (24). Furthermore, Wu et al (47) demonstrated the ability of BRG1, the catalytic core subunit of the SWI/SNF chromatin remodel-FIGURE 3.…”
Section: Discussionmentioning
confidence: 54%
“…Therefore, loss of ARID1A, which frequently occurs in endometrium-related and other carcinomas, may induce an open euchromatin configuration, allowing the transcription of TERT to start. In support of the above observations, a recent study demonstrated that mutation in TERT promoter can epigenetically switch chromatin into an active mode (24). Furthermore, Wu et al (47) demonstrated the ability of BRG1, the catalytic core subunit of the SWI/SNF chromatin remodel-FIGURE 3.…”
Section: Discussionmentioning
confidence: 54%
“…Recently discovered hTERT promoter mutations have been shown to promote telomerase expression by creating additional consensus binding sites for ETS family transcription factors and by triggering an epigenetic switch from inactive to active chromatin at the hTERT promoter (25,26,44). Most cancers, however, reactivate telomerase expression by mechanisms that are independent of promoter mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cancer cells display a pattern of active chromatin marks surrounding the hTERT promoter, thereby allowing transcription factors such as c-Myc to promote expression of the hTERT gene (24). Recently discovered hTERT promoter mutations in human cancer cells have been demonstrated to alter the local epigenetic landscape from a repressive state to open and transcriptionally active chromatin, providing a mechanism that may act as an epigenetic switch at the hTERT promoter (25). However, because most cancers reactivate hTERT gene expression independent of promoter mutations (26), other and currently unknown mechanisms must exist that promote epigenetic changes and create an active chromatin state at the hTERT promoter during cancer development in humans.…”
Section: Significancementioning
confidence: 99%
“…34,39 Functionally, as shown in multiple cell lines, the 2124C>T TERT promoter mutation causes an epigenetic switch from an inactive to active chromatin mark leading to recruitment of GABPA/B1 transcription factor at the site. 40 The 2146C>T mutation in the TERT promoter, on the other hand, has been shown to be driven by noncanonical NF-kB signaling. 41 Incidentally, in melanoma both 2124C>T and 2146C>T mutations occur at almost similar frequencies; in all other malignancies the former mutation is overwhelmingly predominant.…”
Section: Cancer Genetics and Epigeneticsmentioning
confidence: 99%